Habilidades de pensamiento científico: una estrategia didáctica basada en trabajos prácticos - Vargas Guerrero, Martha Andrea; Cifuentes Arcila, María Cristina (Revista Científica, 2011)
This research present a qualitative is guided by the question: How does a teachingstrategy in the Development of Scientific Thinking Skills children attending sixth grade at Colegio Hacienda Los Alcaparros? Two factors justify this research: the need to consider pedagogic practice as a space for reflection and production of educational knowledge and the need to generate teaching to fit the peculiarities of educational situations. The 22 participants in this study are aged between 11 and 13 years old and belong to the socio-economic strata 5 and 6 of the city of Bogotá. The research approach is qualitative, interpretive approaches supported by Erickson (1989). The results indicate that the teaching strategy worked to the extent that enabled the development of ScientificThinking Skills in students the skills to manage and evaluation of evidence and the construction and justification of conclusions for a hearing was held differentially in each ofthe cases studied.